Why Communicative Approach Culturally Fails in Indonesia: Ketidakberhasilan Pendekatan Komunikatif secara Budaya di Indonesia - Masduqi, Harits; Fatimah, Fatimah; Subiyanto , Arif (Journal of Literature and Education, 2024)
For decades, the Indonesian government has tried to catch up with the development of English language teaching worldwide. This paper discusses the implementation of the communicative approach (CA) and why it is culturally incompatible in Indonesia. Having done library research, the writers first discuss the status of English language teaching in Indonesia and the development of communicative language teaching (CLT) in the world. The discussion then shifts to cultural issues hindering the implementation of CLT in Indonesia. Here, instead of suggesting major changes, the writers recommend that CLT be culturally adjusted, and English teachers who play an important role in the classroom must be able to tinker with their methods to make them appropriate to the local cultural norms. There is a pressing need to redefine the current teacher-student relationship to keep up with the prevailing cultural norms. The teachers should incorporate more student-centered activities in the classroom.